Analysis of pickup/deposit stations and dwell point locations in bi-directional flow-rack AS/RSs. Issue 20 (18th October 2022) - Liu, Tian; Gong, Yeming; Zou, Bipan
Abstract : A traditional flow-rack automated storage and retrieval system stores unit-loads in storage lanes with the same slope. This paper considers a new bi-directional flow-rack automated storage and retrieval system, in which adjacent storage lanes slope to opposite directions. While such a system can conduct a dual-command cycle, it is critical to operate the system in an efficient way. We focus on both the pickup/deposit (P/D) station policy and the dwell point location policy, considering two scenarios for each policy. We first build a single-command and a dual-command travel time models for each examined P/D station policy and dwell point location policy. Then, we validate the accuracy of the analytical models by simulation, and theoretically compare the examined P/D point policies and dwell point location policies, in terms of both single-command and dual-command cycle times. We find that locating both the P/D station and the dwell point location at the midpoint of the rack is the best policy. We prove the advantage of the BFR AS/RSs over the traditional flow-rack AS/RSs in terms of single-command cycle time, and that of the dual-command cycle over the single-command cycle. Two case studies are also conducted to examine the effectiveness of the examined policies.